(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The paper aims at providing providers of open and distance learning with information on what is needed if an open and distance learning institution is to provide a productive and sustainable service. The paper premises its discussion on the principle of ‘First things First’ as a strategy to achieve productive and sustainable open and distance learning. There are institutions facing operational challenges because students are shunning them due to dissatisfaction with service delivery. Their dissatisfaction relates to components in the delivery system which can be addressed before service delivery to ensure productivity and sustainability of the service. The paper is based on literature analysis of articles that highlight challenges of providing open and distance learning. The paper concludes that open and distance learning provision is a system which requires all components to be well positioned to enable the system to operate productively and sustainably. It also concludes that if all components are in place, open and distance learning can provide service to learners at any level of educational engagement.